2020
DOI: 10.1115/1.4048995
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation of a Central Fuel Property Hypothesis Under Boosted Spark-Ignition Conditions

Abstract: In the present work, a central fuel property hypothesis (CFPH), which states that fuel properties are sufficient to provide an indication of a fuel's performance irrespective of its chemical composition, was numerically investigated. In particular, the objective of the study was to determine whether Research Octane Number (RON) and Motor Octane Number (MON), as fuel properties, are sufficient to describe a fuel's knock-limited performance under boosted spark-ignition (SI) conditions within the framework of CFP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 58 publications
1
4
0
Order By: Relevance
“…Similar to Szybist et al, 6 Pal et al 20 also showed that along with the RON and MON, laminar burning velocity has a significant influence on the knocking phenomena as well. However, the effects of HoV on knocking was not investigated by Pal et al 17,20 Bestel et al 21 performed experiments and 3-D CFD modeling of CFR engine, adapting the realistic CFR engine model from Pal et al 17 The end gas auto ignition was compared between pipeline natural gas and reference methane/hydrogen blends. The 3-D CFD results in this work 21 revealed that (a) the end gas temperature is higher for methane/hydrogen blend and (b) the turbulent flame velocity is similar for both pipeline natural gas and reference methane/hydrogen blends.…”
Section: Introductionsupporting
confidence: 66%
See 1 more Smart Citation
“…Similar to Szybist et al, 6 Pal et al 20 also showed that along with the RON and MON, laminar burning velocity has a significant influence on the knocking phenomena as well. However, the effects of HoV on knocking was not investigated by Pal et al 17,20 Bestel et al 21 performed experiments and 3-D CFD modeling of CFR engine, adapting the realistic CFR engine model from Pal et al 17 The end gas auto ignition was compared between pipeline natural gas and reference methane/hydrogen blends. The 3-D CFD results in this work 21 revealed that (a) the end gas temperature is higher for methane/hydrogen blend and (b) the turbulent flame velocity is similar for both pipeline natural gas and reference methane/hydrogen blends.…”
Section: Introductionsupporting
confidence: 66%
“…Probst et al 19 utilized the virtual CFR engine model 17 to demonstrate a concurrent perturbation method (CPM) to speed up CFD simulations for predicting cycle-to-cycle variability (CCV) in engine knock. In another recent work, Pal et al 20 used the virtual CFR engine model to determine the corresponding knock-limited spark advance (KLSA) and 50% burn point (CA50) at the respective KLSA timing for gasoline surrogates blended with di-isobutylene (DIB), isobutanol, and anisole.…”
Section: Introductionmentioning
confidence: 99%
“…This model demonstrates good predictive capability in terms of root-mean-square errors (RMSEs) in RON/MON of ∼1 octane number (ON). Further details of the design, implementation, and validation of the neural network can be found in ref . In contrast, TPRF–ethanol (TPRFE) blends were generated utilizing the correlation developed by Al Ramadan et al The data set for TPRFE blends was adopted from our previous study .…”
Section: Numerical Model and Fuel Matrixmentioning
confidence: 99%
“…This allows for better characterizing the fuel–engine interactions. Further, it is well established in the literature that the combustion and emission characteristics of gasoline-like fuels to a large extent are governed by their physical and chemical properties, such as vapor pressure, viscosity, heat of vaporization (HoV), specific heat, research octane number (RON), and octane sensitivity ( S ). Here, octane sensitivity ( S ) is defined as the difference in RON and motor octane number (MON). Van Dam et al performed a global sensitivity analysis to characterize the importance of various physical properties of fuel on the performance of a direct-injection spark-ignition (DISI) engine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation